ANALYSIS OF STUDENTS' DIFFICULTY IN UNDERSTANDING ENGLISH PROVEBS - Prayudha S., Joko (Teaching English as Foreign Language, Literature and Linguisticss, 2023)
Proverb is one of the oldest literary works in the world. Proverb contains messages, values, morals, and advice that can give meaning to life. Many students have difficulty understanding the meaning of a proverb, so the teacher needs to provide appropriate teaching regarding the meaning conveyed in a proverb. This study aims to analyze students' difficulties in understanding the meaning of English proverbs when studying English literature. The method used in this research is qualitative through a descriptive approach. Participants in this study consisted of 35 students who studied English proverbs in English literature class. Data were obtained through documentation, observation, and interviews regarding the difficulty in understanding the meaning of English proverbs. Data were analyzed through data reduction, data display, and conclusion. The results of the study show that students are still confused about explaining the implied meaning of a proverb. This is because knowledge about the pragmatic meaning and sociolinguistic meaning of figurative sentences is still low, so the teacher needs to explain in detail the implied meaning of a proverb. Then, so that students can better get the message conveyed, the teacher asks students to provide examples of these proverbs in everyday life so that the value or advice from a proverb can be used as knowledge in living life.